About a treated rectal cancer: Previous presentation - Badano Repetto, José L.; Antiga, Enrique; Bounous, Ernesto; Costas, Nelly; Chiossoni, Martha; Pizzoli, Adela; Milstein, Isaía; Paperán, Juan; Venturino, Walter (Cirugía del Uruguay, 1978)
The authors present a cancer of rectum (non differentiated carcinoma) with liver metastasis which could not be resected by surgical exploration. Biochemical politherapy made resection of primitive lesion possible· three months later. Histological study showed marked sclerous reaction which suffocated tumoral cells. 7 months after politherapy was begun, regression of liver metastasis became apparent.